An Analysis of Emission Exhaust Gas on 4-Stroke Engine Based on IOT Gas Analyzer - Mokhammad Khatami; Agus Sujatmiko; Asrori Asrori (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
According to the Air Quality Live Index (AQLI), Indonesia's air quality has continued to deteriorate in the last two decades, so Indonesia is officially ranked 17th as the country with the worst air quality in the world. This is due to the population explosion in Indonesia causing industrial activity to also increase. The high levels of exhaust emissions in vehicles, of course, requires the need for technology to measure vehicle exhaust gases to reduce the impact of air pollution. However, the procurement of exhaust emission test equipment is still expensive, so only certain class workshops have this tool. In addition, the reading results of the vehicle's OBD (On Board Diagnostic) system are only able to display the condition or reading value of the Lambda sensor because other gas sensors readings such as CO2, HC, and CO cannot be displayed on the OBD reading results. The purpose of this study is to describe the design of the tool and the results of measuring CO and HC levels through the Blynk application. Research methods that use several gas sensors, such as MQ-7 and TGS-2602 (CO gas) and MQ-2 and TGS-2611 (HC gas), are then compared with the measurement results of a standard gas analyzer. The results showed that the MQ-7 value is close to the accuracy at 1000 rpm and 5000 rpm, namely 99.68% and 99.49%, while the level of accuracy at 3000 rpm is 99.37%. The TGS-2602 sensor at 1000 rpm only has the best accuracy and accuracy, namely 99.67% and 99.77%. The level of accuracy of the MQ-2 sensor has the best value at 1000 rpm rotation, which is 95.71% and the level of accuracy has the highest value at 7000 rpm rotation, which is 100%. For the level of accuracy of the TGS-2611 sensor, it has an accuracy level of 1000 rpm rotation of 94.65% and the level of accuracy of the sensor obtains very good values ​​at 1000 rpm, 7000 rpm, and 9000 rpm rotation of 100%.